ANALYSIS OF MARGIN, ASSET TURNOVER, AND FINANCIAL LEVERAGE ON PROFITABILITY OF AN AGRICULTURE COMPANY - Alhania Farahanny Sofyan; Oktofa Yudha Sudrajad; Erman Arif Sumirat (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The agricultural industry plays a crucial role in Indonesia’s economy, contributing to both economic growth and food security. This research determines the effect of margin, asset turnover, and financial leverage on the profitability of PT. Japfa Comfeed Indonesia from 2015 to 2024 period. PT. Japfa Comfeed Indonesia is a leading agri-food company in Indonesia. Profitability in this research is measured using Return on Equity. This research employs explanatory research with a quantitative approach. Data analysis is conducted using the Multiple Linear Regression method, along with F-tests and t-tests, applied through the SPSS version 29 software. The findings indicate that margin, asset turnover, and financial leverage simultaneously have a significant effect on the company’s profitability. Margin has a significant positive effect on profitability, asset turnover has a significant positive effect on profitability, while financial leverage has a negative but not significant effect on profitability.